TUPOKSI APOTEKER DALAM PENJAMINAN MUTU PRODUK KOSMETIK SESUAI KETENTUAN CPKB DI INDUSTRI FARMASI KOSMETIK - Sukmarani, I Gusti Ayu Putu (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 10 No 2 (2020): Indonesian Journal of Legal and Forensic Sciences, 2020)
Cosmetics are a preparation or product for women and men that are used on the outside of the human body. The cosmetic industry implements an operational system in producing cosmetics by ensuring the quality and safety of cosmetic products to be produced. A cosmetic industry in producing cosmetics must comply with the standard requirements for the quality of cosmetic products that have been determined in accordance with the CPKB (Good C Manufacturing Practices). CPKB is a basic feasibility guideline according to the requirements aimed at making a cosmetic industry produce safe, useful and quality products. Pharmacists who work as QA ( Quality Assurance ) in the pharmaceutical industry for quality assurance of cosmetic products. The benefit of this article is the role of pharmacists in quality assurance of cosmetic products according to GCMP provisions in the cosmetic pharmaceutical industry. The purpose of this article is to determine the role of pharmacists in the quality assurance of cosmetic products contained in the GCMP. The method in this article is literature study using sources, guidelines, references regarding the main duties and functions of a pharmacist. Quality Assurance (QA) functions to ensure that product quality remains during the shelf-life to distribution processes, ensures that self-inspection or quality audits are in accordance with procedures, ensures suppliers of the starting materials used and the packaging are evaluated in accordance with the provisions in order to meet quality requirements. The task of pharmacists as quality assurance is to regulate the design, manufacture and development of products in accordance with applicable regulations, implement the product manufacturing process to comply with the provisions, ensure that the supply of materials, use of starting materials, manufacture and packaging are correct.